2021
DOI: 10.1186/s12958-020-00685-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABO blood groups with ovarian reserve, and outcomes after assisted reproductive technology: systematic review and meta-analyses

Abstract: Background There has been an interest in the relationship between ABO blood groups and infertility. Many studies have investigated the association of ABO blood groups with diminished ovarian reserve (DOR), ovarian hyperstimulation syndrome (OHSS), and outcomes of assisted reproductive technology (ART), with controversial results. Methods A systematic review and meta-analysis was conducted to evaluating the association of ABO blood groups with DOR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…As we indicated, there is no significant relationship between the ABO blood grouping and the onset of menopause. A systematic review and meta-analysis published in 2021 reflected no effect of the ABO blood group on the diminishing of the ovarian reserve [34].…”
Section: Discussionmentioning
confidence: 99%
“…As we indicated, there is no significant relationship between the ABO blood grouping and the onset of menopause. A systematic review and meta-analysis published in 2021 reflected no effect of the ABO blood group on the diminishing of the ovarian reserve [34].…”
Section: Discussionmentioning
confidence: 99%
“…[18] In a meta-analysis examining ABO/Rh blood groups and infertility status or ovarian reserve, the opposite result was found, and it was determined that infertility and assisted reproductive technology were not affected by ABO/Rh blood groups. [19] In another study evaluating 35,479 infertile women, it was found that decreased ovarian reserve increased in women with B blood group and decreased in women with O blood group. [20] In addition, there are studies examining the relation between ovarian cancer and ABO blood groups in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Mu et al found that ABO blood type was associated with ovarian reserve in Chinese women with subfertility [ 22 ]. A meta-analysis showed that there was no significant difference in the incidence of DOR between blood group A/B/AB/non-O and blood group O [ 48 ]. Therefore, more clinical studies are needed to prove this deduction.…”
Section: Discussionmentioning
confidence: 99%